Counterdeception principles and applications for national security - Bennett, Michael; Waltz, Edward (Artech House, Inc., 2007)
Today, more than ever, the use of denial and deception (D & D) is being used to compensate for an opponent?s military superiority, to obtain or develop weapons of mass destruction, and to violate international agreements and sanctions. Although the historical literature on the use of strategic deception is widely available, technical coverage of the subject is scattered in hard-to-find and out-of-print sources. This is the first technical volume to offer a current, comprehensive and systematic overview of the concepts and methods that underlie strategic deception and, more importantly, to provid